Rootbound: Exploring Production in Seattle's Urban Forest - Boetjer, Scott (My University, 2015)
Scott Boetjer Rootbound: Exploring Production in Seattle’s Urban Forest Abstract The urban forest of Seattle provides many benefits and values to its inhabitants. Trees in particular play significant environmental and social roles in the city by cleaning polluted air and water, providing shelter from sun and rain, beautifying our streets, and protecting pedestrians. There are also physical products we extract from our urban forest vegetation, but these remain limited to mulch, some foods, firewood, and compost. Yet despite these important attributes there remains potential to manipulate the urban forest for our changing needs. This project will present four concepts designed to enhance urban forest productivity. The first three are strategic proposals with a broad aim to improve ecological health and forest resiliency in a future of changing climatic conditions. The fourth, Rootbound, is a set of experimental interventions designed to incorporate innovative product development within social and environmental contexts. The current plan for Seattle’s urban forest clearly indicates the goal of its managers; to increase tree canopy and maintain an overall healthy forest. By implementing several new strategic proposals, the urban forest may play a more active role in enhancing ecological and social health. The first is a biochar program using mulch as the feedstock. Up to 90% of urban forest trees are recycled as wood chips and this low-value product can be converted to a high-valuable climate change reduction component. The second proposal will use the urban forest as a seed bank for developing long term resiliency. Heirloom street trees will enable the forest to be more responsive to changes in climate and urban conditions. Third, a regional history of timber forestry inspires the reintroduction of board production to residual sites in the urban forest. Centered on education rather than commercial production, timber trials using vigorous urban forest species may set the stage for future infill projects in Seattle. The fourth and final concept, Rootbound, manipulates root growth as a method of revealing natural urban infrastructures while producing viable, artful urban forest products. Tree roots are often the cause of conflict and damage in the urban setting, but they may be forced into specific forms for productive use in our city. This concept will be presented as designed interventions in the context of four distinct urban forest types. These typologies are distilled from varying environmental conditions and land uses and include: dense urban, residential, residual and industrial. The first intervention will attempt to enliven an otherwise barren public space. Tree containers designed to sit up to four people are arranged in an orchard-like pattern. When completely bound by their roots, each tree is removed to reveal a new type of urban furniture intended to improve the public space and create awareness of alternative forest products. The second intervention enhances playground learning by growing “loose parts;” oversized blocks designed to stimulate teamwork and creativity. Third, the Rootbound concept will be applied to an urban wetland restoration project. Trees and other plants have been shown to phytoremediate polluted soils and this intervention will also create useful, artistic products. Finally, the fourth intervention develops an interlocking nurse log system. Urban forest roots grown on a terraced residual site produce biodegradable blocks intended for slope and bank stabilization/restoration projects. The long term projection of these strategies and interventions is to inspire new methods of productive urban forestry and utilize trees and plants to improve environmental and social health in the built environment. By incorporating them into the City of Seattle’s existing Urban Forest Management Plan, our urban forest may begin actively contributing to the broader goal of climate change reduction. Urban forests that exhibit high levels of vegetative growth - such as those found in the Pacific Northwest – should be utilized as a living laboratory for educating, inspiring, and improving the lives of urban forest inhabitants.
Thesis (Master's)--University of Washington, 2015
Keywords: art; experiment; forest; production; roots; urban; Landscape architecture; Landscape architecture